2 3 ( 2 3 2 ) 0 2 3 = 2 3 1 2 3 2 0 2 3
Is the equation above true or false?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since exponents function work from the top to bottom, you can simplify your work by a little. Hint: look at the powers (or base) with 0 or 1 .
how ( 2^3^2) became 2 ^9 please understand
Log in to reply
Because, when evaluating exponents, you work from the top down.
So, 2^3^2 = 2^(3^2) .
Since 3 2 = 9 , hence 2^3^2 ≡ 2 9 .
Notation no allowed I think error syntax you must use the ()) try in calculator
@Karthik Venkata nice solution!!P.S:Where did u learn CS from?PLZ TELL!
Log in to reply
I learnt CS from past 2 years during summer holidays ( not much really ). The only programming languages I know are 'Wolfram Mathematica' and 'Arduino IDE'. There are tons of video tutorials out there on YouTube, go check 'em out, best of luck and have fun !
Log in to reply
ah!good for u!my internet balance is 2gb max so my dad doesn't allow me to watch videos anyway,thanx for replying!
Log in to reply
@Adarsh Kumar – Well you can check out the ebooks, they are helpful too. I suggest you go through O' Reilly books !
Log in to reply
@Venkata Karthik Bandaru – all right!!thanx a lot bud!!!
Adarsh Kumar, i can't get why 0^2^3 becomes 0...
Log in to reply
0 to any positive power becomes 0 again. I hope you are now clear about this.
Log in to reply
in my boook o raise to any power is undefined
am i right or wrong?
this is i the uk
Log in to reply
@Kool Guy – By theory, it is undefined however in calculations and proofs we equate it to 0.
Log in to reply
@Syed Hamza Khalid
–
No. 0 raised to any positive power is 0.
0 raised to any non-positive power is undefined.
GOOD solution
AT LHS it was 2^3^(2^9)^0 there is no multiplicaltion of nine and zero
anything to the 0 power is 1. 1 raised to any power remains 1. While I disagree with tha naswer of 8, the answer is ture: 1 = 1.
In the LHS, the part after the bracket is a power of 0 , therefore equalling 0 , and the bracketed part will be to the power of 0 , therefore equalling 1 . Then we get 2 3 .
In the RHS, there has only been a 1 added to the chain of exponents, so the result will be the same.
Yes, this is the solution I'm looking for. Good job.
i dont understand....
2 3 ( 2 3 2 ) 0 = 2 3 1 = 2 3
why isnt
2 3 1 2 3 2 0 2 3 = 2 3 1 2 3 2 1
Log in to reply
Because 0 2 3 = 0 8 = 0
Log in to reply
Prasun, 0 2 3 = 0 8 = 0 .
What do you mean by LHS and RHS?
Log in to reply
It's an informal shorthand for "Left hand side" and "Right hand side" of an equation respectively (refer to this article ).
This is really easy. Remember that a b c is the same as ( a b ) c . Remember that anything to the zero power is one, and one to the power of anything is one. Eliminating unnecessary daunting-looking bits of the equation: ⋯ 0 2 3 = ⋯ 0 2 3 1 2 3 = 1 2 3 1 3 = 1 3 1 = 1 That looks to be true, doesn't it?
Wrong. a b c = ( a b ) c . 2 3 4 = 2 ( 3 4 ) = 2 8 1 is correct; while 2 3 4 = ( 2 3 ) 4 = 2 ( 3 ⋅ 4 ) = 2 1 2 is wrong.
looking at this from top 0^2^3=0^2^3 nd then 2^3^2=2^3^2 nd then 2^3=2^3^1 so all these value give end number as 8 on both the sides
I don’t think your final statement is true. Can I have some proof?:)
Top to bottom!!! 2 3 ( 2 3 2 ) 0 2 3 = 2 3 ( 2 3 2 ) 0 = 2 3 1 = 2 3 = 8 2 3 1 2 3 2 0 2 3 = 2 3 1 = 2 3 = 8
Thus, 2 3 ( 2 3 2 ) 0 2 3 = 2 3 1 2 3 2 0 2 3 .
Therefore, the answer is True .
anything power zero is equal to 1. so 2^3=8
if we go on playing with powers.. its tough but you see that when we will proceed in this question at some point we will get LHS=2^3^(2^3^2)^0^2^3 we get 2^3^(2^3^2)^0=1(x^0=1) now we can say LHS=1^2^3..........(1) RHS=2^3^1^2^3^2^0^2^3 we get 2^3^1^2^3^2^0=1(x^0=1) now we can say RHS=1^2^3......(2) 1=2 =>LHS =RHS(hence proved
Both get simplified to 2^(3^1) which is just 2^3 making both equal... very easy to do just by looking at it with the big 0 and 1 in there which auto simplifies it.
It should have stopped at 2 3 1
Once a 0 or 1 appears then there's no point of continuing
It says 2^something times 0.. So whole term becomes 2^0=1.. Same on other side..
Wrong. a b c = ( a b ) c . 2 3 4 = 2 ( 3 4 ) = 2 8 1 is correct; while 2 3 4 = ( 2 3 ) 4 = 2 ( 3 ⋅ 4 ) = 2 1 2 is wrong.
Problem Loading...
Note Loading...
Set Loading...
LHS = 2 3 ( 2 3 2 ) 0 2 3 = 2 3 2 9 × 0 = 2 3 9 0 = 2 3 .
RHS = 2 3 1 2 3 2 0 2 3 = 2 3 1 = 2 3 .
As LHS = RHS, the given equation 2 3 ( 2 3 2 ) 0 2 3 = 2 3 1 2 3 2 0 2 3 is indeed true.